Atractylenolide III Improves Mitochondrial Function and Protects Against Ulcerative Colitis by Activating AMPK/SIRT1/PGC-1α - Han, Jieru; Li, Wenhao; Shi, Guangyu; Huang, Yunlei; Sun, Xutao; Sun, Na; Jiang, Deyou (Mediators of Inflammation, 2022)
Ulcerative colitis (UC) is a complex inflammatory bowel disease (IBD) associated with mitochondrial function. Atractylenolide III (AT III) is a natural product with anti-inflammatory effects. The aim of this work is to investigate the protective effect of AT III on UC and its underlying mechanisms. Herein, dextran sulfate sodium- (DSS-) induced mice and lipopolysaccharide- (LPS-) stimulated intestinal epithelial cells (IEC-6) were employed to mimic UC pathologies in vivo and in vitro. The results showed that in DSS-induced mice, AT III significantly reversed the body weight loss, colon length reduction, disease activity index (DAI) increase, and histological damage. The production of proinflammatory factors and reduction of antioxidants in colitis were suppressed by AT III. In addition, we demonstrated that AT III attenuated the intestinal epithelial barrier destruction and mitochondrial dysfunction induced by DSS, which was similar to the in vitro results in LPS-treated IEC-6 cells. The protein levels of p-AMPK, SIRT1, and PGC-1α along with acetylated PGC-1α were also upregulated by AT III in vivo and in vitro. In conclusion, these findings support that AT III may protect against mitochondrial dysfunction by the activation of the AMPK/SIRT1/PGC-1α signaling pathway during UC development.